Novel SLC30A2 mutations in the pathogenesis of transient neonatal zinc deficiency - Taichiro Muto; Yuriko Kawase; Kaori Aiba; Miyuki Okuma; Naoya Itsumura; Shuangyu Luo; Namino Ogawa; Tokuji Tsuji; Taiho Kambe (Wiley, 2023)
ABSTRACT Importance Transient neonatal zinc deficiency (TNZD) occurs in breastfed infants due to abnormally low breast milk zinc levels. Mutations in the solute carrier family 30 member 2 (SLC30A2) gene, which encodes the zinc transporter ZNT2, cause low zinc concentration in breast milk. Objective This study aimed to provide further insights into TNZD pathophysiology. Methods SLC30A2 sequencing was performed in three unrelated Japanese mothers, whose infants developed TNZD due to low‐zinc milk consumption. The effects of the identified mutations were examined using cell‐based assays and luciferase reporter analysis. Results Novel SLC30A2 mutations were identified in each mother. One harbored a heterozygous missense mutation in the ZNT2 zinc‐binding site, which resulted in defective zinc transport. The other two mothers exhibited multiple heterozygous mutations in the SLC30A2 promoter, the first mutations in the SLC30A2 regulatory region reported to date. Interpretation This report provides new genetic insights into TNZD pathogenesis in breastfed infants.